Saving a river why do local government matters - Rola, Agnes C. (Journal of Environmental Science and Management, 2001)
Studies show that rivers die due to improper waste disposal, water pollution from industrial and agricultural use and degradation of the forest reserve. Several Philippine national agencies are tasked to appropriate, control and conserve water resources. Water laws abound, but implementation of these remains a problem. This study investigates the national laws pertaining to river management, and the local implementation of these. The results showed that the Philippines has enough water policies; but that local implementation is lacking. Local government units do not have the needed ordinances for effective river management. The paper demonstrates the use of environmental economics methods to come up with market-based instruments for river management. A case study of a river in Lantapan, Bukidnon was used to illustrate rural household's validation of the river resources. Local political economy can influence the adoption of these types of policy instruments.